Dermal carotenoid measurement is inversely related to anxiety in patients with breast cancer. (18th September 2017) - Li, David G; LeCompte, Gabrielle; Golod, Lev; Cecchi, Gary; Irwin, David; Harken, Alden; Matecki, Amy
Abstract : Breast cancer is the most prevalent malignancy among women worldwide. Increased oxidative stress and poor subjective health outcomes have been associated with increased risk of cancer recurrence and metastasis, but few studies until now have explored the relationship between oxidative stress and chronic stress/anxiety. This study aims to examine the association between anxiety and a potential dermal correlate of oxidative stress in patients with breast cancer. 102 breast cancer patients were enrolled in a cross-sectional study at Highland Hospital, a county hospital in Oakland, California. Each participant's skin carotenoid score (SCS), a potential dermal correlate of oxidative stress, was recorded via Raman spectroscopy. Patient demographics, breast cancer stage, and subjective health measures (anxiety and self-rated health) were ascertained. Multivariate linear regression analysis was performed to quantify any associations between SCS and the above health correlates. Higher levels of skin carotenoids were associated with decreased severity of anxiety, lower BMI, increased servings of vegetables/fruits in daily diet, Hispanic race, lower educational status, and nonsmoking status. Severity of anxiety as graded by the GAD-7 was inversely associated with dermal carotenoid measurements via SCS. Conclusions. Increased levels of oxidative stress as quantified by SCS is associated with greater severity of anxiety. Because chronic stress has been associated with tumor progression, increased recurrence rates, and increased metastatic risk in breast cancer, non-invasive dermal carotenoid measurements could be used as a novel objective correlate of subjective health during cancer treatment.